(untitled) (The Review of Diabetic Studies, 2024)
The educational system and practical settings present a growing number of problems for nursing students. Disparity between theoretical knowledge and its application in training affects nursing students’ sense of empowerment. Students are likely to achieve the intended learning outcomes only in a clinical learning environment. Evaluating the difficulties in the clinical learning setting aids in making the required adjustments to instruction and learning to produce better results. As a result, the researchers were compelled to assess the difficulties nursing students encounter in practical settings. Finding a correlation between the difficulties nursing students have in the clinical learning setting and certain demographic factors is the aim of this study.